2020
DOI: 10.1002/jccs.202000080
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochromic and vapochromic fluorescence of a bulky π‐system: Alkyl chain‐length effects, triplex emission, and differential sensing of aniline vapors

Abstract: The interplay of mechanical grinding and aniline vapor fuming on the fluorescence of the pentiptycene-anthracene-pentiptycene π-conjugated molecules PAP-Cn, where n is 4, 8, 12, or 16 and refers to the number of carbon atom in the terminal alkyl chains, in solid films are reported. The differences and similarities among the four homologs have led to a conclusion of the formation of an emissive triplex state for the ground and fumed films. Thermogravimetric analysis reveals the guest-host molar ratio and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The observed luminescence enhancement can be attributed to a shielding effect of the vapor molecules to molecular oxygen, a good phosphorescence quencher, because a similar or even larger extent of luminescence enhancement can be achieved by blowing nitrogen gas to 1 (Figure a). We then discovered that the vapor of pMDMA, a good electron donor, is able to induce not only a much higher intensity (300% enhancement) but also a color change from blue to cyan (λ max = 489 nm, Figure b) for the luminescence. The cyan luminescence profile remains upon sitting the pMDMA-fumed samples in the air, and the recovery of the initial status of 1 requires heating or vacuum (Figure S11), indicating a tighter binding of pMDMA in the pores of 1 , partly due to its higher boiling point ( T b = 198 °C).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The observed luminescence enhancement can be attributed to a shielding effect of the vapor molecules to molecular oxygen, a good phosphorescence quencher, because a similar or even larger extent of luminescence enhancement can be achieved by blowing nitrogen gas to 1 (Figure a). We then discovered that the vapor of pMDMA, a good electron donor, is able to induce not only a much higher intensity (300% enhancement) but also a color change from blue to cyan (λ max = 489 nm, Figure b) for the luminescence. The cyan luminescence profile remains upon sitting the pMDMA-fumed samples in the air, and the recovery of the initial status of 1 requires heating or vacuum (Figure S11), indicating a tighter binding of pMDMA in the pores of 1 , partly due to its higher boiling point ( T b = 198 °C).…”
Section: Resultsmentioning
confidence: 98%
“…We have recently demonstrated the utility of the bulky H-shaped pentiptycene scaffold in forming molecular solids of stimuli-responsive luminescence. The three-dimensional pentiptycene scaffold is inherently more isotropic than a planar π-component in intermolecular nonbonded interactions. In addition, the U- and V-shaped cavities of the pentiptycene scaffold could accommodate nonspecific intermolecular π–π and C–H···π interactions.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, numerous researchers have developed organic fluorescence reagents equipped with mechanochromism and vapochromism. 13–29 Recently, we reported that N , N ′-dipyrid-3-yl-1,4,5,8-naphthalenediimide (NDI) linked to two tris(pentafluorophenyl)borane (TPFB) ( 1 ) and N , N ′-bis(2-aminobenzophenone)-1,4,5,8-naphthalenetetracarboxylic diimide ( 2 ) formed 2 : 1 and 1 : 1 complexes, respectively, with toluene as single crystals with fluorescence based on the charge transfer interaction (Fig. 1).…”
mentioning
confidence: 99%